Inhibition of acute leukemia with attenuated Salmonella typhimurium strain VNP20009 - Meirong Li (Biomedicine & Pharmacotherapy, 2020)
Acute leukemia is a common hematological malignancy. Despite recent promising progress, the prognosis of acute leukemia patients remains to be improved. New therapies are therefore still needed. Salmonella typhimurium has been shown to be highly effective as an anti-tumor agent in many solid cancer models, but it has not been applied in acute leukemia. Here, we report an attenuated Salmonella typhimurium strain, VNP20009, can induce apoptosis in multiple types of leukemia cells both in vivo and in vitro. Furthermore, VNP20009 significantly inhibited the proliferation of MLL-AF9-induced acute myeloid leukemia cells and prolonged the survival of the AML-carrying mice. VNP20009 restored the counts of white blood cell (WBC) and its five subsets in peripheral blood (PB) to near-physiological values, and elevated the levels of certain cytokines, such as tumor necrosis factor-α (TNF-α), leukemia inhibitory factor (LIF), interferon-γ (IFN-γ), chemokine C-X-C motif ligand-10 (CXCL-10) and C-C motif ligand-2 (CCL-2). Moreover, the ratio of immune cells, including natural killer cells (NKs), CD4+ Th1-type cells and CD8+ IFN-γ-producing effector T cells were highly upregulated in the AML mice treated with VNP20009. The results of the present study potentially provide an alternative therapeutic strategy for hematologic malignancies through boosting the innate and adaptive anti-tumor immunity.